Lack of Evidence of COVID-19 Being a Risk Factor of Alopecia Areata: Results of a National Cohort Study in South Korea - Kim, Jeehyun; Hong, Kwan; Gómez Gómez, Raquel Elizabeth; Kim, Soojin; Chun, Byung Chul (Frontiers in Medicine, 2021)
Background: Concerns about alopecia areata (AA) in coronavirus disease 2019 (COVID-19) patients have emerged among dermatologists. However, most of extant literature have limited implications by relying on cross-sectional studies with restricted study subjects without control group. Objective: Our study aims to investigate the risk of developing AA among COVID-19 patients in South Korea using national representative data. Methods: We used the National Health Insurance Service (NHIS) COVID‐19 cohort database, comprising COVID‐19 patient and control group, all of whom were diagnosed from January 1, 2020 to June 4, 2020. Patients were defined as individuals who were confirmed as COVID‐19 positive, regardless of disease severity. Controls were defined as whom confirmed as COVID‐19 negative. People with a history of AA during the period 2015–2019 were excluded. The primary endpoint was a new diagnosis of AA (ICD-10- Code: L63). Adjusted incidence rate ratio (IRR) of developing AA was estimated using log-link Poisson regression model based on incidence density. The model adjusted for (1) age and sex, and (2) demographic variables (age, sex, place of residence, and income level). Results: A total of 226,737 individuals (7,958 [3.5%] cases and 218,779 [96.5%] controls) were included in the final analysis. The ratio of newly diagnosed AA was 18/7,958 (0.2%) in cases and 195/218,779 (0.1%) in controls. IRRs of COVID-19 patients having newly diagnosed AA compared to controls were 0.78 (95% Confidence Interval [CI]: 0.48‒1.27) when age and sex were adjusted for, and 0.60 (95% CI: 0.35‒1.03) when all demographic variables were adjusted for. Conclusion: Diagnosis of COVID-19 was not significantly associated with development of AA even after appropriately adjusting for covariates.